2006
DOI: 10.1158/0008-5472.can-05-2744
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Up-regulates Neuropeptide Y Y1 Receptor Expression in a Human Breast Cancer Cell Line

Abstract: Normal breast tissue mainly expresses the neuropeptide Y (NPY) Y2 receptor whereas primary human breast carcinomas express the Y1 receptor (Y1R) subtype. We hypothesized that activation of estrogen signaling systems plays a role in the induction of Y1R. To investigate this possibility, we used estrogen receptor-positive (ER+) human breast carcinoma cell line, MCF-7, and examined the effect of estrogen on Y1R gene expression and its signaling pathways. Saturation binding studies revealed that MCF-7 cells expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 43 publications
5
58
0
Order By: Relevance
“…Further, our studies showed that the activation of Y1R attenuates estrogen-induced cell proliferation in MCF-7 (17).…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Further, our studies showed that the activation of Y1R attenuates estrogen-induced cell proliferation in MCF-7 (17).…”
Section: Introductionsupporting
confidence: 52%
“…Our recent findings showed that human breast cancer cell line MCF-7 expresses functional Y1R, which mobilizes intracellular Ca 2+ and decreases cyclic AMP (cAMP) accumulation in response to NPY stimulation (17). Further, our studies showed that the activation of Y1R attenuates estrogen-induced cell proliferation in MCF-7 (17).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations